Early Postnatal Metabolic Profile in Neonates With Different Birth Weight Status: A Pilot Study - Beken, Serdar; Abali, Saygin; Yildirim Saral, Neslihan; Guner, Bengisu; Dinc, Taha; Albayrak, Eda; Ersoy, Melike; Kilercik, Meltem; Halici, Muge; Bulbul, Ezgi; Kaya, Didem; Karabay, Melis; et al. (Frontiers in Pediatrics, 2021)
Introduction: Restricted or enhanced intrauterine growth is associated with elevated risks of early and late metabolic problems in humans. Metabolomics based on amino acid and carnitine/acylcarnitine profile may have a role in fetal and early postnatal energy metabolism. In this study, the relationship between intrauterine growth status and early metabolomics profile was evaluated. Materials and Methods: A single center retrospective cohort study was conducted. 361 newborn infants were enrolled into the study and they were grouped according to their birth weight percentile as small for gestational age (SGA, n=69), appropriate for gestational age (AGA, n=168) and large for gestational age (LGA, n=124) infants. In all infants amino acid and carnitine/acylcarnitine profile with liquid chromatography-tandem mass spectrometry (LC-MS/MS) were recorded and compared between groups. Results: LGA infants had higher levels of glutamic acid and lower levels of ornithine, alanine and glycine (p<0.05) when compared to AGA infants. SGA infants had higher levels of alanine and glycine levels when compared with AGA and LGA infants. Total carnitine, C0, C2, C4, C5, C10:1, C18:1, C18:2, C14-OH and C18:2-OH levels were significantly higher and C3 and C6-DC levels were lower in SGA infants (p<0.05). LGA infants had higher C3 and C5:1 level; and lower C18:2 and C16:1-OH levels (p<0.05). There were positive correlations between free carnitine and phenylalanine, arginine, methionine, alanine and glycine levels (p<0.05). Also a positive correlation between ponderal index and C3, C5-DC, C14, C14:1; and a negative correlation between ponderal index and ornithine, alanine, glycine, C16:1-OH, C18:2 were shown. Conclusion: We demonstrated differences in metabolomics possibly reflecting the energy metabolism in newborn infants with intrauterine growth problems in the early postnatal period. These differences might be the footprints of metabolic disturbances in future adulthood.